Three-dimensional limit equilibrium analysis of open pits - Lu, H.H.; Fredlund, M.D.; Fredlund, D.G. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The analysis of slope stability in the design and ongoing operations of any particular open pit remains a difficult challenge. Slope failures and loss of equipment, mining time, and lives make stability concerns an issue which warrants research efforts. Engineers have relied for decades on software tools to perform analysis of the slopes of open pits in order to estimate the Factor of Safety (FS). Usually open pit geometry is typical three-dimensional (3D) geometry which cannot adequately be simplified into a two-dimensional (2D) plane strain representation. Traditional analysis has been performed using 2D limit equilibrium methods (LEM) since this method continues to be the simplest to apply. This paper examines the application of the 3D LEM to analyse the slopes of an open pit. The 3D LEM has advantages in that it can consider slips at any particular azimuth vector angle (i.e. it can search the whole 3D open pit model and find the critical slip surface, and critical slip vector). The results of 3D LEM are compared with results from 2D LEM analysis. The result is a methodology which is credible and applicable within a reasonable time frame for the analysis of open pits.